Molecular characterization of human respiratory syncytial virus subtype B: A novel genotype of subtype B circulating in China. Issue 1 (9th June 2014) - Ren, Luo; Xiao, Qiuyan; Zhou, Lili; Xia, Qiuling; Liu, Enmei
<x xml:space="preserve">Abstract</x> Human respiratory syncytial virus (HRSV) is major pathogen of lower respiratory tract infections in infants and young children worldwide. There have been many studies regarding HRSV subgroup A (HRSV‐A) G protein genetic variability but little information about HRSV subtype B (HRSV‐B) G protein genetic diversity and molecular evolution in China. Thus, a survey of the molecular epidemiology and evolution of the G protein in China is of high importance. In this study, the circulation and genetic diversity of HRSV in Chongqing, Southwestern China, from June 2009 to May 2013, were investigated. A total of 3, 167 nasopharyngeal aspirates were obtained in this study, and it was found that HRSV‐B predominated in the 2009–2010 and 2012–2013 epidemic seasons. This study identified the genetic variability of the glycoprotein G gene among 102 HRSV‐B strains isolated by cell culture from Chongqing nasopharyngeal aspirates, and 68 Chinese HRSV‐B sequences were deposited in GenBank. Genotyping and phylogenetic analysis revealed that the HRSV‐B strains were clustered into three genotypes: BA (n = 111, 65.29%), GB3 (n = 5, 2.94%), and a new GB genotype (n = 54, 31.77%) named GB5. The GB5 strains varied from other genotypes in the central conserved region and N‐glycosylation sites. The estimated evolutionary rate of Chinese HRSV‐B was 2.01 × 10−3 nucleotide substitutions/site/year, which is similar to the reports from Belgium and the Netherlands with 1.95 × 10−3 and 2.78 × 10−3 nucleotide substitutions/site/year, respectively. This study provides data on the circulating pattern and molecular characterization of HRSV‐B genotypes in China during four consecutive years and may contribute to HRSV vaccine development. J. Med. Virol. 87: 1–9, 2015. © 2014 Wiley Periodicals, Inc.